GENDER TREND IN 'PELAKOR' DYSPHEMIA: A SOCIOLINGUISTIC STUDY (BIAS GENDER DALAM DISFEMIA ‘PELAKOR’: TINJAUAN SOSIOLINGUISTIK) - Beslina Afriani Siagian; Mhd. Pujiono; Nurilam Harianja (Universitas PGRI Sumatera Barat, 2023)
Dysphemia 'pelakor' is an expression of negative emotions that distort meaning which is currently a global issue. This study focuses on the form, meaning, type, and function of the ‘pelakor’ dysphemia. In addition, the focus is also on the existence of gender bias in the dysphemia so that it will be reviewed with a Sociolinguistic Approach. This study uses a qualitative framework that obtains 8 data from print media, 13 data from electronic media, and 7 data from social media. Data collection was done by sorting out the expression of 'pelakor' dysphemia and then analyzing it in three stages, namely, reduction, presentation, and data verification. The results of the study show that 'pelakor' is in the form of negative emotional expressions, meaning contempt, type of nickname, and functions to humiliate others. In addition, pelakor dysphemia is used to characterize women's identity which is very low and bad and is displayed with anger. There is a gender bias in 'pelakor' dysphemia which is mapped into three points, a) occurs due to male dominance, b) is influenced by culture and social status, c) is conveyed by the women's community. This finding is concluded based on the variation of the language used by women and to describe women. This research is expected to be theoretical and practical contribution in improving gender inequality in Indonesia.